Determining Charge Distribution of Metal Oxide Surfaces With Afm Using Colloid Probe Technique - Güler, Ayşe; Polat, Mehmet (Izmir Institute of Technology, 2012)
Colloidal systems of micron-sized particles dispersed in a solvent are widely encountered in numerous industries. Homogeneity, dispersibility, rheology and forming characteristics of these systems depend solely on particles-particle interactions which in turn are determined by Van der Waals (vdW) and Electrical Double Layer (EDL) forces. The vdW forces are not affected by system chemistry. However, the EDL forces, which arise from the charging of on solid surfaces in a solvent, vary significantly with solution chemistry. So, manipulation of electrical forces is used widely in industrial applications to manipulate colloidal systems. Colloidal particles in solution carry a distribution of positive, negative and neutral charges depending on solution chemistry. Electrophoretic potential mesurements or colloidal titration methods yield only an average charge for the whole population, not the charge distribution on each particle surface. The streaming potential techniques also provide an average charge on the surface. Currently, there is no accepted technique to determine the charge distribution on solid surfaces. This work aims at using Atomic Force Microscopy (AFM) as a charge probe to achieve exactly this. The work improves on a recent study (Yelken, 2010) which used commercial SiN4 cantilevers to determine the charge distribution on quartz and sapphire surfaces by replacing SiN4 cantilevers with custom-made colloid probes of desired material (quartz in this case) to probe the surface. The current work which improves the flexibility and resolution of the method was tested with two quartz and
Thesis (Master)--Izmir Institute Of Technology, Chemical Engineering, Izmir, 2012
Includes bibliographical references (leaves: 86-89)
Text in English; Abstract: Turkish and English
xvi, 103 leaves
Keywords: Surface chemistry; Atomic force microscopy; Surfaces (Technology)--Analysis; Intermolecular forces